CUSTOMS AND TRADITIONS OF USA - Otaqulova Gulirano Yoshuzoq qizi (Journal of new century innovations, 2022)
Annotation: In this article you can read about some customs and traditions of USA. American culture encompasses the customs and traditions of the United States.